Emerging platinum(IV) prodrug nanotherapeutics: A new epoch for platinum-based cancer therapy - Zheng, Shunzhe; Li, Guanting; Shi, Jianbin; Liu, Xinying; Li, Meng; He, Zhonggui; Tian, Chutong; Kamei, Ken-ichiro (Journal of Controlled Release, 2023)
Owing to the unique DNA damaging cytotoxicity, platinum (Pt)-based chemotherapy has long been the first-line choice for clinical oncology. Unfortunately, Pt drugs are restricted by the severe dose-dependent toxicity and drug resistance. Correspondingly, Pt(IV) prodrugs are developed with the aim to improve the antitumor performance of Pt drugs. However, as “free” molecules, Pt(IV) prodrugs are still subject to unsatisfactory in vivo destiny and antitumor efficacy. Recently, Pt(IV) prodrug nanotherapeutics, inheriting both the merits of Pt(IV) prodrugs and nanotherapeutics, have emerged and demonstrated the promise to address the underexploited dilemma of Pt-based cancer therapy. Herein, we summarize the latest fronts of emerging Pt(IV) prodrug nanotherapeutics. First, the basic outlines of Pt(IV) prodrug nanotherapeutics are overviewed. Afterwards, how versatile Pt(IV) prodrug nanotherapeutics overcome the multiple biological barriers of antitumor drug delivery is introduced in detail. Moreover, advanced combination therapies based on multimodal Pt(IV) prodrug nanotherapeutics are discussed with special emphasis on the synergistic mechanisms. Finally, prospects and challenges of Pt(IV) prodrug nanotherapeutics for future clinical translation are spotlighted. This review summarizes the latest fronts of Pt(IV) prodrug nanotherapeutics with specific focus on how Pt(IV) prodrug nanotherapeutics overcome the multiple drug-delivery biological barriers and Pt(IV) prodrug based multimodal combination therapy. [Display omitted]